Assessment of volatile profile as potential marker of chilling injury of basil leaves during postharvest storage. (15th December 2016) - Cozzolino, Rosaria; Pace, Bernardo; Cefola, Maria; Martignetti, Antonella; Stocchero, Matteo; Fratianni, Florinda; Nazzaro, Filomena; De Giulio, Beatrice
Highlights: Seventy-one VOCs were identified by SPME in the headspace of basil samples. VOCs as potential biomarkers of chilling injury in basil leaves were explored. Comprehensive data analysis was based on PLS regression models. Correlation between VOCs profile and chilling injury parameters was achieved. Abstract: The volatile profile of three sweet basil cultivars, "Italico a foglia larga", "Cammeo" and "Italiano classico", packaged in air at 4 or 12 °C until 9 days, was monitored by solid phase microextraction with GC–MS. Chilling injury (CI) score and electrolyte leakage were also assessed. In total, 71 volatile organic compounds (VOCs) were identified in the headspace of basil samples. A preliminary principal component analysis highlighted the dominant effect of the cultivar on VOCs profiles. Data analysis by post-transformation of projection to latent structures regression (ptPLS2) clarified the role played by time and temperature of storage. Temperature influenced the emission of volatiles during storage, with much lower total volatile emissions at 4 °C compared to 12 °C. Finally, a ptPLS2 regression model performed on VOCs and the two CI parameters allowed selection of 10 metabolites inversely correlated to both CI parameters, which can be considered potential markers of CI in basil leaves.